Analisis Pengaruh Kualitas Pelayanan dan Biaya terhadap Kepuasan Peserta Kursus pada LKP Lestari Komputer - Sri Lestari; Fahrudin Fahrudin; Toto Sudibyo; Nurkhayati Nurkhayati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of service quality and cost on course participants’ satisfaction at LKP Lestari Komputer. The research employs a quantitative approach using a survey method through questionnaires distributed to 50 active course participants from September to October 2025. The independent variables consist of service quality (X₁) and cost (X₂), while the dependent variable is participants’ satisfaction (Y). Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26. The regression equation obtained is Y = -4.572 + 0.742X₁ + 0.287X₂. The t-test results show that service quality (t = 5.221; sig = 0.000) and cost (t = 2.538; sig = 0.015) have a positive and significant effect on participants’ satisfaction. The F-test result shows an F value of 49.180 with a significance level of 0.000, indicating that service quality and cost simultaneously have a significant effect on participants’ satisfaction. The coefficient of determination (R²) of 0.672 indicates that 67.2% of the variation in participants’ satisfaction is explained by both variables.